A microbial-based biochar, a microbial-based single-atom iron catalyst, and preparation methods and applications thereof
By using microorganisms as biochar precursors, microbial-based biochar rich in N heteroatoms are prepared, and single-atom iron is loaded to form Fe-C-N structures, the problems of low activity and high cost of existing fuel cell catalysts are solved, and the problem of low energy efficiency and high cost of existing fuel cell catalysts is achieved. Highly efficient, low-cost and stable microbial-based single-atom iron catalyst.
Patent Information
- Application Number
- CN202311771676.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-12-20
AI Technical Summary
The existing fuel cell catalysts have low activity in oxygen reduction reaction (ORR), and precious metal catalysts such as Pt-based catalysts are costly and have poor stability, making it difficult to meet the requirements of high efficiency, low cost and stability.
Using microorganisms as the precursor of biochar, microbial-based biochar rich in N heteroatoms is obtained through morphological regulation and carbonization processes, and single-atom iron is chemically supported to form a Fe-C-N structure to prepare a microbial-based single-atom iron catalyst. .
It has achieved low-cost, high catalytic activity and stability, and has better performance than commercial platinum carbon catalysts, has high oxygen reduction catalytic activity, methanol resistance and stability, and has the potential to replace precious metal catalysts.
Smart Images

Figure CN118004993B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of bio-based carbon materials, and specifically relates to a microbial-based carbon material, a microbial-based single-atom iron catalyst, and a preparation method and application thereof. Background Art
[0002] In the past few decades, with the increase in the number of humans and the rapid development of science and technology, the use of fossil fuels has greatly improved people's living standards. However, most fossil fuels are non-renewable, and the emissions generated during the use of fossil fuels will pollute the environment. With the rapid development of industrial industries in recent years, it is increasingly necessary to use energy devices that are clean, pollution-free and efficient. Fuel cells are widely used because of their advantages such as clean and pollution-free environment, not limited by the Carnot cycle, high energy density, and no noise. It is an energy conversion device with great development potential and application prospects. However, fuel cells in the prior art also have shortcomings. At the cathode, due to the poisoning effect of anions in the electrolyte on the activity of oxygen reduction reaction (ORR), the catalyst forms a compound with no catalytic activity through adsorption behavior, resulting in a slow ORR rate of the fuel cell. This adsorption behavior is very sensitive to changes in the surface structure of the catalyst and can change in a reversible or partially reversible manner, and this adsorption change will cause the active sites on the catalyst surface to be blocked. Moreover, compared with the high-rate hydrogen oxidation (HOR) reaction on the anode, the cathode needs to add a high level of oxygen reduction catalyst to increase the reaction rate. However, even with the best Pt catalyst currently available, the ORR reaction kinetics are about 5 orders of magnitude lower than the anode HOR. Moreover, Pt-based catalysts are also more expensive and prone to catalyst poisoning due to their poor stability during the catalytic process, further limiting the application of fuel cells.
[0003] In order to solve these problems, it is urgent to develop non-precious metal catalysts with low cost, abundant reserves, high catalytic activity and stability. The study of transition metal and nitrogen co-doped carbonaceous (MNC) catalysts is one of the most important research directions in the field of oxygen reduction catalysis in recent years, and has the potential to replace precious metal catalysts. Among them, biochar-based catalysts prepared with biochar as carbonaceous material have the advantages of low cost, high specific surface area, good conductivity and stability. Biochar can be prepared by direct pyrolysis of precursors from natural plants and animals. Since the biological residues themselves contain elements such as N, O, and P, no additional heteroatom-containing reagents are required in this process to obtain heteroatom (C, N, O, P, etc.) doped carbon catalysts. The original biochar material shows poor activity in the ORR process, but after doping with transition metal atoms (e.g., iron and cobalt) or non-metal atoms (e.g., nitrogen, phosphorus, sulfur, and boron), its ORR activity is expected to be enhanced due to the regulatory effect caused by the different electronegativity and atomic size of the dopant. This allows biochar-based catalysts to have similar or even higher electrochemical activity than precious metal catalysts while being low-cost, and its stability and methanol resistance are very good. The common method of preparing biochar is to carbonize plants at high temperatures, but plants have low protein content and low overall nitrogen content, so it is not easy to obtain a large number of CN structures after carbonization. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned defects and shortcomings in the prior art and to provide a method for preparing microbial-based biochar.
[0005] The second object of the present invention is to provide a method for preparing a microbial-based single-atom iron catalyst.
[0006] The third object of the present invention is to provide the microbial-based biochar and the microbial-based single-atom iron catalyst.
[0007] The last object of the present invention is to provide applications of the microbial-based biochar and the microbial-based single-atom iron catalyst.
[0008] The above-mentioned object of the present invention is achieved through the following technical solutions:
[0009] The present invention first provides a method for preparing microbial-based biochar, which includes firstly controlling the morphology of microorganisms to prevent bacterial bodies from agglomerating and hardening, then freezing and drying to obtain microbial powder, and then carbonizing the microbial powder to obtain the microbial-based biochar.
[0010] The present invention creatively selects microorganisms as precursors of biochar. Compared with plants, microorganisms are rich in heteroatoms such as N, O, P, etc., and a large number of CN structures can be obtained by carbonization. The structure has high catalytic activity, and the rich N atoms can effectively increase the oxygen reduction catalytic ability of the catalyst. Furthermore, in order to increase the specific surface area and conductivity of the biochar carrier, the present invention first controls the morphology of the microbial precursor to prevent the bacteria from agglomerating and compacting, thereby ensuring that it will not agglomerate together after subsequent high-temperature carbonization, and can form biochar with a porous loose structure. In addition to having good conductivity, it can also make the transition metal Fe more evenly distributed on the surface of the biochar, further forming an Fe-CN structure, thereby further improving the catalytic activity of the obtained microbial-based single-atom iron catalyst.
[0011] Furthermore, the microorganism is a microorganism with high nitrogen content.
[0012] Furthermore, the microorganism is a microorganism with a high Fe-N structure content, and its cell membrane surface contains a large amount of cytochrome c, carries iron porphyrin groups, and contains a certain Fe-N structure. The Fe-CN structure has high catalytic activity and can effectively increase the oxygen reduction catalytic ability of the catalyst.
[0013] Preferably, the microorganism is a bacterium of the genus Shewanella.
[0014] More preferably, the microorganism is Shewanella oneidensis MR-1.
[0015] The present invention takes Shewanella oneidensis MR-1 as an example, takes the bacterial body of Shewanella oneidensis MR-1 as the precursor for biochar synthesis, and performs morphology control to increase the specific surface area and conductivity of the microbial material, and then carbonizes it, thereby preparing a microbial-based biochar with a porous surface, rich in N heteroatoms, and good conductivity. The surface of the Shewanella oneidensis MR-1 is rich in nitrogen atoms, and it contains a certain amount of heme and a certain amount of iron atoms.
[0016] Furthermore, the modifier is sodium chloride.
[0017] Furthermore, the morphology control comprises centrifuging and washing the microbial cell culture solution, and mixing the obtained cell with a saturated sodium chloride solution.
[0018] Furthermore, the volume ratio of the microbial cell culture solution to the saturated sodium chloride solution is 24-26:1.
[0019] Furthermore, the freezing and drying are freezing at -38°C to -42°C for 0.8 to 1.2 hours and freeze drying for 1 to 3 days.
[0020] Preferably, the freezing and drying are freezing at -40°C for 1 hour and freeze-drying for 2 days.
[0021] In morphology control, carbonization at too low a temperature will prevent the modifier from completely blending with the microorganisms, causing microbial agglomeration, while too high a temperature may cause the heteroatoms in the microorganisms to volatilize during the carbonization process, resulting in a decrease in oxygen reduction catalytic activity.
[0022] Therefore, further, the carbonization temperature is 810-1000°C.
[0023] Preferably, the carbonization temperature is 900°C.
[0024] Furthermore, the carbonization operation is: heating to 900° C. at a heating rate of 10° C. / min and heating for 3 hours.
[0025] A microbial-based biochar is prepared by the above preparation method.
[0026] The present invention further loads iron atoms on the surface of the above-mentioned microbial-based biochar by chemical methods to obtain a microbial-based single-atom iron catalyst in the form of a single atom (cluster). During the carbonization process of the catalyst, Fe species will not agglomerate to form iron oxides, but will be evenly dispersed on the surface of the microbial carbon in the form of single iron atoms and atoms such as N and O, and rich nitrogen is distributed around the iron, forming the Fe-CN active center; after electrochemical test characterization, it was found that under alkaline conditions, the microbial-based single-atom iron catalyst prepared by the present invention has better ORR catalyst performance than the commercially commonly used platinum-carbon catalyst, and has high oxygen reduction catalytic activity, methanol resistance and stability.
[0027] Therefore, the present invention also provides a method for preparing a microbial-based single-atom iron catalyst, comprising adding the above-mentioned microbial-based biochar and iron salt to ultrapure water and mixing them evenly, first adding aniline, stirring and then adding ammonium persulfate to obtain a mixed solution; after adjusting the pH of the mixed solution to acidic, carbonizing the precipitate to obtain the microbial-based single-atom iron catalyst.
[0028] Furthermore, the usage ratio of the microbial-based biochar, aniline and ammonium persulfate is (24-26): (0.08-0.12): (0.8-1.2).
[0029] Furthermore, the iron salt is FeCl3.
[0030] Furthermore, the usage ratio of the microbial-based biochar, FeCl3, aniline and ammonium persulfate is (24-26): (7-8): (0.08-0.12): (0.8-1.2).
[0031] Preferably, the usage ratio of the microbial-based biochar, FeCl3, aniline and ammonium persulfate is 25:7.8:0.1:1.
[0032] Furthermore, the pH is 2.0 to 3.0.
[0033] Preferably, the pH is 2.3.
[0034] Furthermore, the stirring after adding aniline is stirring at room temperature, and the stirring time is 30 minutes.
[0035] Furthermore, the carbonization temperature is 800-1000°C.
[0036] Preferably, the carbonization temperature is 900°C.
[0037] Furthermore, the carbonization operation is: heating to 900° C. at a heating rate of 10° C. / min and heating for 2 hours.
[0038] A microbial-based single-atom iron catalyst is prepared by the above preparation method.
[0039] Finally, the present invention provides the use of the microbial-based biochar and / or the microbial-based single-atom iron catalyst in catalyzing oxygen reduction reactions.
[0040] The microbial biochar and / or the microbial-based single-atom iron catalyst are used in the preparation of fuel cell catalysts.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The present invention uses microorganisms as precursors of biochar. Compared with plants, microorganisms are rich in heteroatoms such as N, O, P, etc., and a large number of CN structures can be obtained, which have a larger specific surface area and better conductivity; further, Fe single atoms are synthesized by chemical methods, loaded on the surface of the microbial-based biochar, and form Fe-NC active centers with the abundant nitrogen in the microorganisms, thereby preparing a microbial-based single-atom iron catalyst. The microbial-based single-atom iron catalyst is low in price, simple in process, has better catalytic performance than commercial platinum-carbon catalysts, has high catalytic activity, and also has methanol resistance and stability, and has the potential to replace precious metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1The figures are scanning electron microscope (SEM) images of the materials obtained by carbonizing Shewanella MR-1 bacteria, wherein (a) is a SEM image of the material obtained by direct carbonization of MR-1 bacteria; (b) is a SEM image of the material obtained by carbonizing MR-1 bacteria after CaCO3 treatment; (c) is a SEM image of the material obtained by carbonizing MR-1 bacteria after KOH treatment; (d) is a SEM image of the material obtained by carbonizing MR-1 bacteria after NaCl treatment; (e) is a further enlarged SEM image of the material obtained by carbonizing MR-1 bacteria after NaCl treatment.
[0044] Figure 2 This is the linear sweep voltammetry (LSV) diagram of MR-Fe-PAIN-900 with different Fe contents.
[0045] Figure 3 LSV diagrams of catalyst MR-0.5Fe-PAIN-900 prepared at different temperatures.
[0046] Figure 4 This is the high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and energy dispersive spectroscopy (EDS) surface scan of the catalyst MR-Fe-PAIN-900.
[0047] Figure 5 Infrared spectra of catalysts MR-Fe-PAIN-900 and MR-NaCl.
[0048] Figure 6 X-ray diffraction spectra (XRD) of catalysts MR-Fe-PAIN-900 and MR-NaCl.
[0049] Figure 7 These are the peaks of C1s, N1s and O1s in the X-ray photoelectron spectrum (XPS) of the catalyst MR-Fe-PAIN-900.
[0050] Figure 8 Cyclic voltammetry (CV) diagrams of catalysts MR-NaCl and MR-Fe-PAIN-900.
[0051] Fig. 9 LSV diagrams of catalysts MR-NaCl, MR-Fe-PAIN-900 and Pt / C 20%.
[0052] Fig.10 The LSV diagram of catalyst MR-Fe-PAIN-900 at different rotation speeds.
[0053] Fig.11 is the number of electron transfer of catalyst MR-Fe-PAIN-900 at different voltages.
[0054] Fig.12 It is the Tafel plot of catalysts MR-Fe-PAIN-900 and Pt / C 20%.
[0055] Fig.13 This is the LSV diagram of catalyst MR-Fe-PAIN-900 before and after adding methanol.
[0056] Fig.14 This is the LSV diagram of catalyst Pt / C 20% before and after adding methanol.
[0057] Fig.15 This is the LSV diagram of catalyst MR-Fe-PAIN-900 before and after 6000 cycles.
[0058] Fig.16 LSV of the catalyst D@Fe-PAIN-900, which was prepared by loading iron on rice husk biochar using the aniline method, at different rotation speeds.
[0059] Fig.17 The electron transfer number of catalyst D@Fe-PAIN-900 at different voltages was prepared by loading iron on rice husk biochar using the aniline method.
[0060] Fig.18 LSV of the catalyst M@Fe-PAIN-900, which was prepared by loading iron on cotton stalk biochar using the aniline method, at different rotation speeds.
[0061] Fig.19 The electron transfer number of the catalyst M@Fe-PAIN-900 prepared by loading iron on cotton stalk biochar using the aniline method at different voltages. DETAILED DESCRIPTION
[0062] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0063] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0064] The catalytic activity, stability, methanol resistance and electron transfer number of the catalyst can be known by electrochemical characterization. The electrochemical workstation used in the following examples is CHI 660E, which adopts a three-electrode system, and the working electrode, auxiliary electrode and reference electrode are platinum carbon electrode, platinum sheet electrode and Ag / AgCl electrode respectively. Before the test, the rotating disk electrode used needs to be cleaned and polished, ultrasonicated for 30 minutes, and finally the electrode is dried for use.
[0065] The preparation method of the working electrode is as follows: weigh 10 mg of sample with an analytical balance and put it into a 5 mL centrifuge tube, then add 1 mL of isopropanol, 3.98 mL of deionized water and 0.02 mL of Nafion solution, shake the centrifuge tube to mix evenly, and then put it into an ultrasonic machine for 30 minutes. Wait until the catalyst is completely and evenly dispersed in the solution, take 2 μL of solution with a pipette, and slowly drip it into the center of the working electrode, do not let the solution overflow, turn on the rotating disk electrode, rotate at a speed of 500 rpm, until the solution is completely air-dried, continue to take 2 μL of solution and drip it, repeat the above operation 3 times, that is, a total of 6 μL of solution is dripped into the working electrode, wait until the solution containing the catalyst is air-dried and set aside. Another method is to carefully blow dry the working electrode with a hair dryer.
[0066] In the following examples, the oxygen reduction reaction activity of the catalyst was tested by linear voltammetry (LSV), and the specific parameters were as follows: the rotation speed was set to 1600 rpm, the electrolyte was 0.1 M KOH, the scanning range was 0.2-1.15 V (vs. RHE), and the scanning speed was 5 mv s -1 . The entire LSV curve is similar to an "S" shape, with a "platform" at both ends of the first part. We divide it into three parts, which are controlled by kinetics, kinetic-diffusion mixing and diffusion respectively. The current density at the diffusion control is called the limiting current (JL), and the potentials corresponding to 5% and 50% of the limiting current are called the starting potential (Eonset) and the half-wave potential (E1 / 2), respectively. These three parameters are the main parameters for measuring the ORR activity of the catalyst. Before the test, oxygen is first introduced into the electrolyte for at least half an hour to create an oxygen-filled environment.
[0067] Shewanella oneidensis MR-1 was purchased from Marine Microbial Culture Collection Center, with the culture collection number ATCC700550.
[0068] Example 1 Preparation and characterization of microbial-based biochar
[0069] Direct carbonization of MR-1 bacteria: In an ultra-clean workbench, use an inoculation loop to inoculate the MR-1 strain of Shewanella oleracea in the solid culture medium into 500 mL of LB culture medium and seal it with a sealing film. Cultivate in a constant temperature shaker (30°C, 180 rpm) for 24 hours to obtain MR-1 culture solution; centrifuge (8000 rpm, 3 min), wash with ultrapure water 3 times; freeze at -40°C for 1 hour, freeze-dry for 2 days to obtain MR-1 powder; carbonize the dried MR-1 in a tubular furnace for 3 hours (900°C, 10°C / min), wash with ultrapure water 3 times, and dry at 60°C to obtain MR-1 biochar.
[0070] MR-1 cells were carbonized after being treated with CaCO3: 500 mL of MR-1 cells cultured in LB medium were centrifuged and washed, 10 mL of ultrapure water was added to the obtained cells, and then 1.47 g of CaCl2·2H2O and 2.86 g of Na2CO3·10H2O were added. After mixing, they were frozen at -40°C for 1 hour, freeze-dried for 2 days, and then carbonized in a tubular furnace for 3 hours. The cells were washed with ultrapure water 3 times and dried at 60°C to obtain MR-CaCO3 biochar.
[0071] MR-1 cells were treated with KOH and then carbonized: MR-1 cells cultured in 500 mL of LB medium were centrifuged and washed, and the obtained cells were freeze-dried. The dried MR-1 was mixed with KOH in a ratio of 1:1, carbonized in a tubular furnace for 3 hours, washed with ultrapure water, and dried to obtain MR-KOH biochar.
[0072] MR-1 cells were treated with NaCl and then carbonized: MR-1 cells cultured in 500 mL of LB medium were centrifuged and washed, the obtained cells were mixed with 20 mL of saturated sodium chloride solution, frozen at -40°C for 1 hour, freeze-dried for 2 days to obtain powder, carbonized in a tube furnace for 3 hours, washed with ultrapure water, and dried to obtain MR-NaCl biochar.
[0073] The MR-1 biochar, MR-CaCO3 biochar, MR-KOH biochar and MR-NaCl biochar prepared above were subjected to SEM test. The results are as follows Figure 1 As shown, Figure 1 a is the SEM image of MR-1 without any treatment after carbonization at 900℃. It can be seen that the carbonized MR-1 has been completely agglomerated and lacks pores; Figure 1 b is the SEM image of MR-CaCO3 obtained after treatment with CaCO3. It can be seen that CaCO3 does not have a good pore-forming effect; Figure 1 c is the SEM image of MR-KOH obtained after KOH treatment, which shows that many macropores are formed on the surface of biochar in a honeycomb shape, but the pore size is too large, reaching the micrometer level, and a large number of small pores do not appear; Figure 1 d is the SEM image of MR-NaCl obtained after NaCl treatment. It can be seen that the material prepared by this method has a porous loose structure full of wrinkles. Figure 1 As shown in Fig. e, the whole material is in a fluffy state. This structure may enable the transition metal Fe to be more evenly distributed on the surface of biochar to form a Fe-CN structure.
[0074] Example 2 Preparation of microbial-based single-atom iron catalyst
[0075] 25 mg of MR-NaCl biochar prepared in Example 1 and 7.8 mg of FeCl3 were uniformly dispersed in 20 mL of ultrapure water, 0.1 g of aniline was added, stirred at room temperature for 30 minutes, and 1 g of ammonium persulfate was added. The solution was adjusted to pH 2.3 with 0.5 M HCl, stirred at room temperature for 24 hours, centrifuged (8000 prm, 5 min), dried at 100 ° C overnight, and carbonized in a tubular furnace for 2 hours (900 ° C, 10 ° C / min) to obtain the oxygen reduction catalyst MR-Fe-PAIN-900.
[0076] Example 3: Exploration of Preparation Parameters of Microbial-Based Single-Atom Iron Catalysts
[0077] (1) Exploring the amount of transition metal ion Fe added as a catalyst
[0078] According to the preparation method of Example 2, MR-0.5Fe-PAIN-900 was prepared, wherein the amount of FeCl3 added was 3.9 mg.
[0079] As above, MR-1.5Fe-PAIN-900 was prepared, wherein the amount of FeCl3 added was 11.7 mg.
[0080] The oxygen reduction reaction activity of MR-Fe-PAIN-900 prepared in Example 2 and the above two catalysts was tested by linear voltammetry (LSV). The test results are as follows: Figure 2 As shown. It can be seen that when the amount of ferric chloride added is 7.8 mg, the activity of the catalyst MR-Fe-PAIN-900 is the best. On this basis, increasing or decreasing the amount of ferric chloride added will reduce the activity of the catalyst. When the amount of ferric chloride added becomes 1 / 2 of the original, the active centers of the catalyst will be reduced, resulting in a decrease in catalytic activity. When the amount of ferric chloride added becomes 1.5 times the original, too much ferric chloride will cause iron to agglomerate on the surface of the carbon material, resulting in a decrease in catalytic activity.
[0081] (2) Exploring the optimal reaction temperature
[0082] MR-0.5Fe-PAIN catalysts were prepared at different temperatures (600-1000°C) and named MR-0.5Fe-PAIN-600, MR-0.5Fe-PAIN-700, MR-0.5Fe-PAIN-800, MR-0.5Fe-PAIN-900, and MR-0.5Fe-PAIN-1000, respectively. Their oxygen reduction reaction activities were tested. The test results are shown in FIG. Figure 3 It can be seen that when the reaction temperature is 900°C, the activity of the catalyst is the best, while the starting potential, half-wave potential or limiting current of the catalyst will decrease when the reaction temperature is higher or lower than 900°C.
[0083] In summary, it can be concluded that when the addition amount of ferric chloride is 7.8 mg and the reaction temperature is 900°C, the reaction activity of the catalyst is the best.
[0084] Example 4 Performance Characterization of Microbial-Based Single-Atom Iron Catalyst
[0085] The performance of the microbial-based biochar MR-NaCl prepared in Example 1 and the microbial-based single-atom iron catalyst MR-Fe-PAIN-900 prepared in Example 2 were characterized.
[0086] (1) Structure and element distribution
[0087] The STEM image of MR-Fe-PAIN-900 is as follows: Figure 4 As shown in a, it is shown that MR-Fe-PAIN-900 has a dodecahedral flake structure after carbonization, with a smooth surface and stacked graphene-like ultra-thin layers. Figure 4 b is a high-angle annular dark field scanning TEM image (HAADF-STEM) of the catalyst MR-Fe-PAIN-900. The results are the same as we expected. There is a large amount of uniformly dispersed Fe in MR-Fe-PAIN-900 (see Figure 4 The bright spots circled in red in b) are uniformly loaded on the biochar surface in the form of single atoms or single atom clusters in terms of size. The element distribution and chemical composition of MR-Fe-PAIN-900 were characterized by STEM imaging combined with energy dispersive X-ray spectroscopy (EDS). Figure 4 c to f. The surface of the material is not only rich in C and O, but also rich in N elements. At the same time, Fe elements are scattered on the surface of the material, which is consistent with the iron single atoms (clusters) observed in the HAADF mode. It can be inferred that the material has the conditions to form Fe-CN catalytic active centers. This structure has a great beneficial effect on promoting oxygen reduction catalysis.
[0088] The biochar MR-NaCl prepared by the catalyst MR-Fe-PAIN-900 and the raw material Shewanella MR-1 was in the range of 500-4000cm -1 Infrared spectrum in the range Figure 5 As shown. Figure 5 It can be seen that the characteristic peaks of the raw material MR-1 can be found in the infrared spectrum of the catalyst MR-Fe-PAIN-900. The absorption peak is 1080cm -1 、1200cm -1 and 3405cm -1 They are respectively attributed to HCO, CO and OH stretching vibrations, indicating that oxygen in the material mainly exists in the form of carbonyl, carboxyl and hydroxyl groups. The absorption peak is 1560cm -1It is attributed to the C=N structure, which proves the presence of nitrogen atoms in the biochar carrier prepared by Shewanella MR-1. -1 The peak at corresponds to the typical C≡C stretching vibration, which has a slightly weaker peak intensity due to the molecular symmetry.
[0089] The XRD patterns of the catalyst MR-Fe-PAIN-900 and its precursor MR-NaCl after carbonization are shown in Figure 6 As shown. The diffraction peaks of MR-Fe-PAIN-900 are concentrated at 2θ=26° and 51.8°, which can be attributed to the 002 and 101 crystal planes of typical turbostratic carbon, respectively. In addition, there are no other diffraction peaks in the spectrum, indicating that the catalyst is an amorphous carbon structure. In MR-Fe-PAIN-900, the diffraction peaks of typical iron oxide were not observed, indicating that the Fe on the carrier is highly dispersed and no crystalline minerals are formed. The above results show that during the carbonization process, the Fe species in the catalyst MR-Fe-PAIN-900 will not agglomerate to form iron oxides, but may be uniformly dispersed on the surface of the carrier MR-NaCl in the form of single iron atoms. This structure can provide active sites to the greatest extent and promote the catalysis of oxygen reduction reactions.
[0090] Figure 7 The C1s, N1s and O1s peaks of the catalyst MR-Fe-PAIN-900 were analyzed. The C1s spectrum shows that the sample mainly contains three forms of carbon elements, CC, C=N and C=O, with peak positions of 284.8 eV, 285.8 eV and 290.1 eV, respectively. The presence of elemental oxygen may be mainly due to the adsorbed oxygen and some oxygen-containing groups in the pores of biochar. From the N1s spectrum, it can be seen that the sample mainly contains four forms of nitrogen, CN, Pyridinic-N, Graphitic-N and Fe-N, with peak positions of 392.7eV, 398.4eV, 401.0eV, 403.9eV, and their contents of 4.41%, 23.71%, 54.03% and 18.11%, respectively. It can be seen that the most abundant form of N in the catalyst is graphite N (54.03%), followed by pyridinic N (23.71%), and the presence of 18.11% of Fe-N further indicates that Fe-CN chemical bonds may have been formed. From the O1s spectrum, it can be seen that the sample mainly contains three forms of oxygen, adsorbed oxygen, OC=O and C=O, with peak positions of 530.4eV, 532.8eV, 536.8eV, respectively. According to the results of C1s, N1s and O1s spectra, the Fe atoms in the prepared catalyst MR-Fe-PAIN-900 mainly exist in the form of Fe-N, and the N atoms are successfully combined with the graphite structure of the carbon material, which is also consistent with the above-mentioned infrared spectrum and XRD results.
[0091] (2) Oxygen reduction catalytic activity
[0092] A series of electrochemical characterizations were carried out on the most active catalyst MR-Fe-PAIN-900, starting with CV and LSV characterizations. Figure 8 shown. Figure 8 The cyclic voltammetric characteristics of MR-NaCl and MR-Fe-PAIN-900 were obtained by CV scanning of the catalysts in 0.1M KOH electrolyte filled with O2. Figure 8 It can be seen that both catalysts produce redox peaks, indicating that the two catalysts undergo redox reactions in the 0.1M KOH electrolyte filled with O2. Therefore, it can be preliminarily determined that both catalysts have oxygen reduction catalytic activity.
[0093] Linear voltammetric sweep tests were performed on MR-NaCl, MR-Fe-PAIN-900 and commercial Pt / C 20% catalysts in 0.1M KOH electrolyte filled with O2. The results are shown in Figure 2. Fig. 9 As shown in the figure, both catalysts have oxygen reduction catalytic activity. The catalytic activity of MR-Fe-PAIN-900 loaded with single-atom iron on the basis of MR-NaCl can be greatly improved (E1 / 2 = 0.833V), which is roughly equal to the commercial Pt / C 20% catalyst (E1 / 2 = 0.838V), and the limiting current J = -4.96mA cm -2 It is also better than the commercial Pt / C 20% catalyst J = -4.68mAcm -2 , which is also at a relatively high level among similar Fe-NC electrocatalysts. The above results show that the prepared non-precious metal single-atom catalyst MR-Fe-PAIN-900 has excellent oxygen reduction catalytic activity.
[0094] (3) Reaction pathway and kinetics
[0095] In order to further explore the reaction pathway and kinetics of the catalyst MR-Fe-PAIN-900, the LSV curves of the catalyst at rotation speeds of 500 rpm, 1000 rpm, 1600 rpm, 2600 rpm and 3600 rpm were tested. Fig.10 As shown; further, the LSV curves at different speeds are plotted, and then the limiting current and the corresponding speed are fitted at voltages of 0.3V, 0.4V and 0.5V to obtain Fig.11 Koutecky-Levish (KL) curve graph shown.
[0096] Depend on Fig.10It can be seen that in the LSV curve of the catalyst MR-Fe-PAIN-900 at different speeds, the change of the limiting current is close to an arithmetic progression, which indicates that the oxygen reduction reaction catalyzed by the catalyst is a kinetically controlled oxygen reduction reaction. Fig.11 The KL curve of the catalyst MR-Fe-PAIN-900 was taken at 0.3V, 0.4V, and 0.5V, and the average number of electron transfers in the oxygen reduction reaction catalyzed by the catalyst MR-Fe-PAIN-900 was 3.9, which is very close to the transfer process of 4e-Pt / C, indicating that the reaction pathway of the catalyst is mainly carried out through the 4-electron reaction pathway. The 4-electron reaction is the most efficient reaction mode for the oxygen reduction catalytic reaction, proving that the catalyst has efficient ORR performance.
[0097] The Tafel slopes of the catalyst MR-Fe-PAIN-900 and commercial Pt / C were further analyzed and compared. Fig.12 As shown, the Tafel slopes of the catalyst MR-Fe-PAIN-900 and commercial Pt / C are 86.4 mV dec, respectively. -1 and 84.6mV dec -1 , the two are very close, indicating that the electrocatalytic kinetics of MR-Fe-PAIN-900 and commercial Pt / C catalysts are similar. This also shows that the catalyst MR-Fe-PAIN-900 has good ORR performance. The catalyst can have good ORR catalytic activity, probably because of its high N content and high dispersion density of FeN4 active sites. According to previous reports, the active center of FeN4 in the catalyst can directly react with O2, so that the reaction is more preferentially carried out in 4e-reaction, while inhibiting the generation of 2e-reaction H2O2.
[0098] (4) Methanol resistance
[0099] In order to explore the methanol resistance of the catalyst MR-Fe-PAIN-900, 1M methanol was added during the catalyst reaction and the changes in the LSV curves before and after were compared to evaluate the methanol resistance of the catalyst. Fig.13 As shown in the figure, the catalytic activity of the catalyst MR-Fe-PAIN-900 remains basically unchanged before and after adding methanol, indicating that the catalyst has good methanol resistance and can normally catalyze the oxygen reduction reaction in a methanol environment. For comparison, the same experiment was conducted using a commercial Pt / C 20% catalyst. The results are shown in Fig.14 As shown in the figure, when methanol is added, the catalyst is poisoned, the oxygen reduction catalytic activity of the commercial Pt / C 20% catalyst is greatly reduced, and the methanol resistance is far lower than that of the catalyst MR-Fe-PAIN-900.
[0100] (5) Stability
[0101] In order to explore the stability of the catalyst MR-Fe-PAIN-900, an accelerated aging test (AAT) was performed on it: after the catalyst MR-Fe-PAIN-900 was cycled in alkaline electrolyte for 6000 times, the changes in the LSV curves before and after were compared. The results are as follows: Fig.15 As shown. Fig.15 It can be seen that after 6000 CV cycles, the half-wave potential of the catalyst MR-Fe-PAIN-900 decreased by 36 mV, and the limiting current decreased by -0.5 mA cm -2 , indicating that the catalyst has good stability under alkaline conditions.
[0102] Example 5 Comparison of different plant biochars and microbial-based biochars
[0103] The rice husk biochar was loaded with iron using the aniline method to obtain the catalyst D@Fe-PAIN-900. The LSV test results are as follows: Fig.16 As shown, under the same rotation speed of the rotating disk electrode, the maximum current is less than the microbial carbon in this patent, and the starting potential is lower than the biochar in the present invention (with Fig.10 The electron transfer number of catalyst D@Fe-PAIN-900 at different voltages is shown in Fig.17 As shown, the calculated number of reaction electrons is 2.8, which is less than 3.9 of the present invention (compared with Fig.11 Compare).
[0104] After the cotton stalk biochar was loaded with iron using the aniline method, the catalyst M@Fe-PAIN-900 was obtained. The LSV test results are as follows: Fig.18 As shown, under the same rotation speed of the rotating disk electrode, the maximum current is less than the microbial carbon in this patent, and the starting potential is lower than the biochar in the present invention (with Fig.10 The electron transfer number of catalyst M@Fe-PAIN-900 at different voltages is shown in Fig.19 As shown, the calculated number of reaction electrons is 2.2, which is less than 3.9 of the present invention (compared with Fig.11 Compare).
[0105] The above results show that selecting microorganisms to prepare microbial-based biochar can have better catalytic effects than plant biochar.
Claims
1. A method for preparing a microbial-based single-atom iron catalyst, characterized in that: After adding microbial-based biochar and iron salt to ultrapure water and mixing, aniline is added first, and then ammonium persulfate is added after mixing to obtain a mixed solution; after adjusting the pH of the mixed solution to acidity, the precipitate is carbonized to obtain the microbial-based single-atom iron catalyst; the preparation method of the microbial-based biochar is to first control the morphology of the microorganism to prevent the bacterial body from agglomerating and hardening, then freeze and dry to obtain microbial powder, and then carbonize the microbial powder to obtain the microbial-based biochar; the microorganism is a Shewanella bacterium; the modifier used for the morphology control is sodium chloride.
2. The preparation method according to claim 1, characterized in that: The microorganism is Shewanella oneidensis MR-1.
3. The preparation method according to claim 1, characterized in that: The carbonization temperature is 810-1000°C.
4. The preparation method according to claim 1, characterized in that: The carbonization temperature is 900°C.
5. The preparation method according to claim 1, characterized in that: The iron salt is FeCl3.
6. A microbial-based single-atom iron catalyst, characterized in that: The invention is prepared by any one of the preparation methods of claims 1 to 5.
7. Use of the microbial-based single-atom iron catalyst according to claim 6 in catalyzing oxygen reduction reactions.
Citation Information
Patent Citations
A method of preparing a doped carbon catalytic material by utilizing a microorganism and iron ore
CN106252672A
Fe-N-C ultralow-temperature SCR denitration catalyst as well as preparation method and application thereof
CN116474816A